Acute oral administration of low doses of methylphenidate targets calretinin neurons in the rat septal area - García-Avilés, Álvaro; Albert-Gascó, Héctor; Arnal-Vicente, Isabel; Elhajj, Ebtisam; Sanjuan-Arias, Julio; Sanchez-Perez, Ana María; Olucha-Bordonau, Francisco (Frontiers in Neuroanatomy, 2015)
Methylphenidate (MPD) is a commonly administered drug to treat children suffering from attention deficit hyperactivity disorder (ADHD). Alterations in septal driven hippocampal theta rhythm may underlie attention deficits observed in these patients. Amongst others, the septo-hippocampal connections have long been acknowledged to be important in preserving hippocampal function. Thus, we wanted to ascertain if methylphenidate administration, which improves attention in patients, could affect septal areas connecting with hippocampus. We used low and orally administered methylphenidate doses (1.3; 2.7 and 5mg/Kg) to rats what mimics the dosage range in humans. In our model, we observed no effect when using 1.3mg/Kg methylphenidate; whereas 2.7 and 5 mg/Kg induced a significant increase in c-fos expression specifically in the medial septum, an area intimately connected to the hippocampus. We analyzed dopaminergic areas such as nucleus accumbens and striatum, and found that only 5mg/Kg induced c-fos levels increase. In these areas tyrosine hydroxylase correlated well with c-fos staining, whereas in the medial septum the sparse tyrosine hydroxylase fibres did not overlap with c-fos positive neurons. Double immunofluorescence of c-fos with neuronal markers in the septal area revealed that co-localization with choline acethyl transferase, parvalbumin, and calbindin with c-fos did not change with MPD treatment; whereas, calretinin and c-fos double labeled neurons increased after MPD administration. Altogether, these results suggest that low and acute doses of methylphenidate primary target specific populations of caltretinin medial septal neurons.